Endemicisation of COVID-19: Will it Salvage the Hospitality and Tourism Industry? - Sthapit, Arhan (Nepalese Journal of Hospitality and Tourism Management, 2022)
The proposition of ‘endemicisation’ of COVID-19 is being mooted so that the hospitality and tourism industry that has borne the brunt of the pandemic could be salvaged and compensate for the damage. There are arguments for and against the ‘endemicisation’ bid that is making rounds among the policy makers and stakeholders of this industry.